Identification of Genes Involved in Bacteriostatic Antibiotic-Induced Persister Formation - Cui, Peng; Niu, Hongxia; Shi, Wanliang; Zhang, Shuo; Zhang, Wenhong; Zhang, Ying (Frontiers in Microbiology, 2018)
Persister cells are metabolically quiescent multi-drug tolerant fraction of a genetically sensitive bacterial population and are thought to be responsible for relapse of many persistent infections. Persisters can be formed naturally in the stationary phase culture, and also can be induced by bacteriostatic antibiotics. However, the molecular basis of bacteriostatic antibiotic induced persister formation is unknown. Here, we established a bacteriostatic antibiotic induced persister model and screened the Escherichia coli single gene deletion mutant library for mutants with defect in rifampin or tetracycline induced persistence to ofloxacin. Thirsty-seven and nine genes were found with defects in rifampin- and tetracycline-induced persister formation, respectively. Six mutants were found to overlap in both rifampin and tetracycline induced persister screens: recA, recC, ruvA, uvrD, fis, and acrB. Interestingly, four of these mutants (recA, recC, ruvA, and uvrD) mapped to DNA repair pathway, one mutant mapped to global transcriptional regulator (fis) and one to efflux (acrB). The stationary phase culture of the identified mutants and parent strain BW25113 were subjected to different antibiotics including ofloxacin, ampicillin, gentamicin, and stress conditions including starvation and acid pH 4.0. All the six mutants showed less tolerance to ofloxacin, but only some of them were more sensitive to other specific stress conditions. Complementation of five of the six common mutants restored the persister level to that of the parent strain in both stationary phase and static antibiotic-induced conditions. In addition to the DNA repair pathways shared by both rifampin and tetracycline induced persisters, genes involved in rifampin-induced persisters map also to transporters, LPS biosynthesis, flagella biosynthesis, metabolism (folate and energy), and translation, etc. These findings suggest that persisters generated by different ways may share common mechanisms of survival, and also shed new insight into the molecular basis of static antibiotic induced antagonism of cidal antibiotics.